Edukasi Pemberian Makanan Pendamping ASI (MP-ASI) melalui Whatsapp Group bagi Ibu-ibu di Sangatta, Kalimantan Timur - Pramitasari, Rianita (Yayasan Literasi Sains Indonesia, 2022)
Complementary feeding in infants and children is a challenge for mothers in North Sangatta, East Kalimantan. The purpose of this community service was to provide knowledge to mothers in North Sangatta about complementary feeding and a strategy to deal with children when they do not want to eat via Whatsapp Group. The method used in this program was counseling to increase understanding about complementary feeding and how to deal with children when they do not want to eat. The participants are given material in a pdf format file that can be studied before the event takes place. Then, participants were asked to write the questions. Two days later, the participants and instructor interacted on the Whatsapp Group to answer the questions and respond to the answers. Before giving the material, the participants were given a pre-test questionnaire. Meanwhile, post-test questionnaires were also given after the event was over to determine understanding after giving the material. The program has been running well and smoothly. Participants gain knowledge about complementary feeding and how to deal with children when they do not want to eat. Participants considered that the educational materials were very useful. Participants thought that the material was easy to understand. The presentation was clear and done one time. In addition, they become more confident in dealing with children when they do not want to eat.